Invitro Efficacy of Trichoderma Isolates and Commercial Fungicides against Exobasidium vexans, Causal Agent of Blister Blight in Tea - Adhikari, Karun; Rai, Ashis (International Journal of Applied Sciences and Biotechnology, 2022)
Blister blight is one of the most significant foliar fungal diseases of tea plant caused by Exobasidium vexans. An invitro experimentation on efficacy of biofungicides and chemical fungicides was carried out at Agriculture Research Station, Pakhribas from November 2020 to January 2021 to evaluate and analyze effectivity of two Trichoderma spp and five commonly used chemical fungicides against Blister Blight pathogen. Isolates of Trichoderma viride and Trichoderma harzianum were tested against E. vexans using dual culture technique. Five Chemical fungicides namely Copper oxychloride 50WP, Hexaconazole 5% EC, Metalaxyl 8% WP+ Mancozeb 64% WP, Carbendazim 50% WP, Carboxin 37.5% WS + Thiram 37.5% WS were tested at four different concentrations viz. 50 ppm, 100 ppm, 200 ppm and 500 ppm using poisoned food technique. The experiment was carried out in completely randomized design with three replications for each treatment. Both Trichoderma viride and Trichoderma harzianum demonstrated significant effect on mycelial growth reduction of E. vexans. Trichoderma viride and Trichoderma harzianum exhibited 70.87% and 66.98% inhibition in growth of E. vexans respectively. Similarly, Hexaconazole, Carbendazim, Carboxin + Thiram provided complete (100%) inhibition on pathogen growth regardless of concentration. Least inhibition (36%) on pathogen growth was recorded at 50 ppm of Copper Oxychloride. All chemical fungicides provided significant difference on reducing growth of pathogen in comparison to control at all concentration. It is recommended that Trichoderma spp be taken as a priority regarding its environmental benefit and furthermore if application of chemical fungicides is necessitated, rationalized use be done at lower dose and with appropriate timing.